MARKETING BERKELANJUTAN DALAM PERSPEKTIF FIQH:: Studi Al-Qur’an dan Hadist melalui Analisis Tafsir Maudhu’i terhadap Bisnis yang Berkelanjutan - Ali Kurnia, Candra (Al-Iqtishadiah: Jurnal Hukum Ekonomi Syariah, 2022)
This article aims to identify the concept of sustainable marketing from an Islamic perspective using a thematic analysis approach to the interpretation of the Qur'an and Hadith. Sustainable marketing is a very relevant approach in the modern business world, where business actors are required to consider social and environmental aspects in their operations. From an Islamic perspective, sustainable marketing is closely related to the principles of fiqh that emphasize ethics, social responsibility, and environmental sustainability. Through a thematic study of the verses of the Qur'an and Hadith, this study identifies values ​​such as amanah, honesty, responsibility, and justice that are relevant to the concept. The results of this study are expected to contribute to ethical guidelines in Islamic business, as well as offer a framework for Muslim entrepreneurs to practice ethical and sustainable marketing.